FORECASTING THE NUMBER OF POPULATION IN INDONESIA USING ARIMA METHOD - Hikmah, Rika Nur (Nurjati Journal of Mathematics and Mathematical Sciences (NJMMS), 2024)
This study aims to obtain the right forecasting model to predict the population in Indonesia using the Autoregressive Integrated Moving Average (ARIMA) method and to find out the results of forecasting the Indonesian population for the period 2022-2031. This type of research is descriptive with a quantitative approach. The data collection method used is documentation. The data used is quantitative data in the form of data on the population of Indonesia in 2000-2021 obtained from the official website of the Badan Pusat Statistik (BPS). The data analysis technique in this study used the ARIMA method with the help of Minitab 16 software. The results showed that the best model was the ARIMA model (0.2.2) with an MSE value of 2.4390. The results of forecasting the population of Indonesia in the next 10 periods are 277,022 million people, 280,264 million people, 283,509 million people, 286,757 million people, 290,007 million people, 293,261 million people, 296,517 million people, 299,775 million people, 303,037 million people, and 306,301 million people. With the results of this forecast, it is hoped that the government can take appropriate action to address the rate of population growth in Indonesia, for example through the Keluarga Berencana (KB) program, limiting the age of marriage, improving the quality of education, equitable development, and opening up employment opportunities so that the needs of the population are met by good